ENT Diseases Among Children Presenting To A Teaching Hospital In Sargodha: A Cross-Sectional Analysis - Khan, Muhammad Zubair; Mehr, Shahzad Hanif; Saeed, Munazza; Hussain, Junaid; Mirza, Furqan; Sadiq, Sana Muhammad (Journal of Rawalpindi Medical College, 2025)
Objective: This study aimed to determine the frequency of commonly prevalent pediatric ear, nose, and throat (ENT) disorders presenting in the outpatient department of a teaching hospital in Sargodha, Pakistan. Methods: This cross-sectional study was conducted at the Department of Otorhinolaryngology, Niazi Welfare Foundation Teaching Hospital, from October 1, 2024, to April 30th, 2025. A total of 380 children aged 0–15 years were enrolled via consecutive sampling, after obtaining informed consent from their primary caregivers. SPSS 21 was used for statistical analysis, including the Chi-square test to identify the statistical significance of various study variables. Results: Out of 380 participants, the majority (53.2%) were male and 82.6% lived in rural areas. The most frequently diagnosed disorders were tonsillitis (20.3%), acute suppurative otitis media (9.2%), epistaxis (7.9%), adenotonsillitis (7.9%), and pharyngitis (3.4%). A significant statistical association was found between ENT disorders and age (Contingency Coefficient = 0.927, p < 0.001). Parental education (p<0.001) and smoking exposure (p=0.003) influenced the disease chronicity. Parental inclination towards unverified health care providers was influenced by the education level of both parents (p<0.001), the mother’s occupation (p=0.046) and the father’s occupation (p<0.001). Conclusion: ENT disorders, particularly tonsillitis, are commonly prevalent among children in Sargodha. Low parental education level and exposure to second-hand smoking significantly contribute to disease recurrence. Region-specific, multicenter data collection is essential to provide evidence-based figures for policymakers to plan the provision of healthcare strategies, especially in underserved areas. Keywords: Adenoids, Chronic Otitis media, Epistaxis, Paediatrics, Pharyngitis, Tonsillitis